New taxonomic and faunistic data on the Himalayan Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2016)
New taxonomic and faunistc data for seven species of the genus Lesteva Latreille, 1797 of the Himalayas are presented. Two species are redescribed: L. (s.str.) kargilensis Cameron, 1934 and L. (s.str.) steeli Lohse, 1982. The aedeagus of L. (s.str.) steeli is illustrated. One synonym is proposed: L. (s.str.) brevipennis Cameron, 1941 = L. pakistana Coiffait, 1984 syn. n. A lectotype and paralectotypes for L. (s.str.) torrentum Cameron, 1924 are designated. A key to species known from the Himalayan Region is provided.